2015
DOI: 10.1002/2015ja021639
|View full text |Cite
|
Sign up to set email alerts
|

The nature of GPS differential receiver bias variability: An examination in the polar cap region

Abstract: While modern GPS receiver differential code bias estimation techniques have become highly refined, they still demonstrate unphysical behavior, namely, notable solar cycle variability. This study investigates the nature of these seasonal and solar cycle bias variabilities in the polar cap region using single‐station bias estimation methods. It is shown that the minimization of standard deviation bias estimation technique is linearly dependent on the user's choice of shell height, where the sensitivity of this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
(70 reference statements)
1
33
0
Order By: Relevance
“…These issues are, however, not solely limited to the IRI. Themens et al [2013] demonstrated that the sparsity of data in high-latitude regions contributes to significant errors in the representation of TEC in these regions by global TEC maps, and Themens et al [2015] showed that the strong gradients in TEC at high latitudes significantly degrade the performance of standard Global Positioning System (GPS)-based TEC calibration techniques. Also, Athieno et al [2015] and Athieno and Jayachandran [2016] show that standard HF communication models exhibit significant errors at high latitudes, largely due to errors in the URSI and International Radio Consultative Committee critical frequency maps, which are also used in the IRI.…”
Section: Introductionmentioning
confidence: 99%
“…These issues are, however, not solely limited to the IRI. Themens et al [2013] demonstrated that the sparsity of data in high-latitude regions contributes to significant errors in the representation of TEC in these regions by global TEC maps, and Themens et al [2015] showed that the strong gradients in TEC at high latitudes significantly degrade the performance of standard Global Positioning System (GPS)-based TEC calibration techniques. Also, Athieno et al [2015] and Athieno and Jayachandran [2016] show that standard HF communication models exhibit significant errors at high latitudes, largely due to errors in the URSI and International Radio Consultative Committee critical frequency maps, which are also used in the IRI.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to satellite DCBs, the receiver DCBs are less stable, and their magni- tudes and variations show large differences for different types of receivers. The receiver DCB seems to be related to the temperature around antennas (Coster et al, 2013;Yasyukevich et al, 2015;Themens et al, 2015). Besides its intrinsic variations, the estimated DCB series includes the signal associated with ionospheric anomalous variations and other errors, such as the multipath effect and the high-order effect of ionospheric delay, that are ignored in traditional TEC and DCB estimation, since non-modeling errors will affect the DCB estimation (Petrie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The shell height is taken as the center of mass of the ionosphere above CASSIOPE (Komjathy & Langley, ; Themens et al, ): hshell=hGAPNe()hhnormaldhhGAPNe()hnormaldh where N e ( h ) is the electron density at height h . Electron densities below auroral latitudes are taken from the International Reference Ionosphere (IRI) 2012 empirical model, which provides electron densities up to 2,000 km altitude.…”
Section: Receiver Dcb Estimatementioning
confidence: 99%
“…The shell height is taken as the center of mass of the ionosphere above CASSIOPE (Komjathy & Langley, 1996;Themens et al, 2015):…”
Section: 1002/2017rs006453mentioning
confidence: 99%
See 1 more Smart Citation